Beyond Church and State: Rethinking Who Knew What When About Residential Schooling in Canada - Di Mascio, Anthony (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2013)
This study moves beyond evidence left behind by church and state officials to ask who knew what when about residential schooling in Canada. While our historical knowledge about residential schooling and the people involved in and affected by it has grown in recent years, scholars have characteristically focused on official church and state agents. Other non- Aboriginal individuals who lived in or spent some time in Aboriginal communities, and who are not typically implicated in residential schooling, have consequently been overlooked as a source of knowledge about the truth of residential schooling. By broadening our examination of the various people who knew about residential schooling, by considering what they knew, and by coming to terms with the truth that many of them did little or nothing to stop the abuse they witnessed, this study suggests that we can more fully understand ourselves and our history, and we can be more properly prepared to move forward in a process of reconciliation and healing.